IDENTIFIKASI STRATEGI PEMASARAN MARKETING MIX 7P PADA SEKTOR UMKM - Zailani, Rinawati; Suprihatiningsih, Suprihatiningsih (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This research aims to analyze the implementation of the 7P marketing mix strategy for small and medium enterprises "Mazzy Craft" in Kapanewon Bantul, Bantul Regency. Small and Medium Enterprises (MSMEs) are defined as small businesses owned and run by individuals or small groups. The research method used is a qualitative method with data collection using interviews and documentation. The research results show that the marketing strategy used by "Mazzy Craft" uses the 7P marketing mix strategy: Product, by creating product innovation by developing previously existing products and prioritizing quality, uniqueness, packaging and product innovation. Price, is determined according to the level of difficulty of product production and the amount of raw materials used. Promotion, carried out online with the help of social media and participating in exhibitions. Place, marketing carried out offline and online and product delivery using shipping expeditions or according to customer requests. People, "Mazzy Craft" makes its business a job opportunity for everyone and does not carry out special selection, but employs individuals who have skills or abilities in accordance with the parts needed. Physical Evidence, provides comfort and security for employees and consumers, although in the field it still needs improvement. Process, consisting of service, product creation, ordering, payment transfer, packaging and product delivery